1972
DOI: 10.1128/am.23.3.490-499.1972
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Newly Developed Latex Agglutination Test and an Immunodiffusion Test in the Diagnosis of Systemic Candidiasis

Abstract: A newly developed latex agglutination (LA) test and a modified immunodiffusion (ID) test were evaluated. The antigen used was a homogenate of Candida albicans . A total of 167 antisera were employed in the evaluation. They included 36 sera from clinically well persons; 78 from patients with various clinical forms of candidiasis; 52 from patients with proven cases of aspergillosis, blastomycosis, coccidioidomycosis, cryptococcosis, histoplasmosis, nocardiosis, paracoccidioidomycosis, spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Recent studies (3, 5, 10-12, 14, 17, 20-22) have shown that the detection of agglutinating and precipitating antibody to extracts of Candida species indicates Candida infection. Tests using a cytoplasmic antigen preparation seem especially predictive of systemic candidiasis, including Candida endocarditis (10,11,17,20).Even with early diagnosis, therapy with amphotericin B alone is rarely sucessful, and valve replacement is necessary for cure. Amphotericin B and 5-fluorocytosine (5-FC) in combination have been reported to be synergistic in vitro with some strains and have been successfully used in several patients without valve replacement (E. Rubinstein et al, Program…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (3, 5, 10-12, 14, 17, 20-22) have shown that the detection of agglutinating and precipitating antibody to extracts of Candida species indicates Candida infection. Tests using a cytoplasmic antigen preparation seem especially predictive of systemic candidiasis, including Candida endocarditis (10,11,17,20).Even with early diagnosis, therapy with amphotericin B alone is rarely sucessful, and valve replacement is necessary for cure. Amphotericin B and 5-fluorocytosine (5-FC) in combination have been reported to be synergistic in vitro with some strains and have been successfully used in several patients without valve replacement (E. Rubinstein et al, Program…”
mentioning
confidence: 99%
“…Recent studies (3, 5, 10-12, 14, 17, 20-22) have shown that the detection of agglutinating and precipitating antibody to extracts of Candida species indicates Candida infection. Tests using a cytoplasmic antigen preparation seem especially predictive of systemic candidiasis, including Candida endocarditis (10,11,17,20).…”
mentioning
confidence: 99%
“…DISCUSSION Candidiasis is the most common fungal infection in compromised hosts, a situation made more ominous by the difficulty in establishing antemortem diagnosis (2-5, 7, 9, 10). Although the DID technique for candida serum precipitin detection has been shown to be of great specificity, it may take from 24 to 96 h for a positive reaction to be discernible (8,(13)(14)(15). Remington et al ( 12) demonstrated the detectio7n of candida serum precipitins by CIE in patients with significant candidiasis.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical features: Denture stomatitis may be graded clinically into three types. (stickle, Kaufman and Blumer, 1972) Type I: Pinpoint hyperaemia and diffuse inflammation of a limited area of the mucosa in an otherwise normal tissue.…”
Section: Menon and Ganapathymentioning
confidence: 99%